Perancangan Sistem PPDB Berbasis Web Pada Yayasan Pendidikan Islam Manarul Huda Dengan Metode Agile - Yunus, Muhammad Ayub; Hadiansyah, Idham Nursyifa; Muhaziz, Taufiq; Haryono, Wasis (Jurusan Informatika STTR Cepu, 2025)
This study discusses the design of a web-based New Student Admission (PPDB) information system at the Manarul Huda Islamic Education Foundation. The system was developed to replace the manual registration process, which is prone to data entry errors, delays, and inefficient information management. The Agile methodology was applied to ensure a flexible and iterative development process that adapts to user needs. The design process involved user requirement analysis, system modeling using Unified Modeling Language (UML), database normalization, and limited system testing. The implementation results show that the system significantly improves registration efficiency, reduces administrative workload, and provides faster and more transparent access to information for both prospective students and the foundation. The system received positive feedback for its ease of use and structured flow. This research is expected to serve as a reference for similar system developments in other educational institutions.